2011
DOI: 10.1007/s00300-011-1020-3
|View full text |Cite
|
Sign up to set email alerts
|

Sea water transport and submersion tolerance as dispersal strategies for the invasive ground beetle Merizodus soledadinus (Carabidae)

Abstract: International audienceThe alien ground beetle Merizodus soledadinus was introduced to the sub-Antarctic Kerguelen Islands in 1913. It colonized several small islands and islets of this archipelago, without any apparent human assistance in some locations, and crossed several large rivers and alluvial plains. As aggregations of this species on the tidal drift line are common at the Kerguelen Islands, the present work examined whether adult individuals of M. soledadinus could disperse by flotation on the sea. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, even with the likelihood that human assistance has played a role in further spreading the beetle after its arrival in the vicinity of the research station, this is unlikely to explain all instances of local colonisation by the beetle, for instance of several islands of the Golfe du Morbihan that are rarely visited. Rather, as suggested earlier, beetles are likely to have arrived by rafting on vegetation or algae 81,82 or through ornithochory. For instance, Kerguelen shags Phalacrocorax verrucosus use seaweeds that they sometimes transport from one island to another when building their nests.…”
Section: Absentmentioning
confidence: 86%
See 1 more Smart Citation
“…However, even with the likelihood that human assistance has played a role in further spreading the beetle after its arrival in the vicinity of the research station, this is unlikely to explain all instances of local colonisation by the beetle, for instance of several islands of the Golfe du Morbihan that are rarely visited. Rather, as suggested earlier, beetles are likely to have arrived by rafting on vegetation or algae 81,82 or through ornithochory. For instance, Kerguelen shags Phalacrocorax verrucosus use seaweeds that they sometimes transport from one island to another when building their nests.…”
Section: Absentmentioning
confidence: 86%
“…2) by marine rafting. While the distance from Port-Couvreux to Anse Sablonneuse is 25 km overland, it is only 400 m by direct line crossing the inlet, and experimental data have revealed that M. soledadinus can survive flotation and exposure to saline conditions for several days 81,82 .…”
Section: Historical Documentation Of the Invasionmentioning
confidence: 99%
“…Even if direct flight to islands is not the dominant form of colonisation, flight may promote arrival by drift as carabids collected from drift material are predominantly winged (Karjalainen 2000; Kotze and Niemelä 2002), and thus are likely to have been blown into water during flight. Colonisation ability may also include survival ability of carabids in lake water (see Renault 2011), although it is unknown how this may vary with body size. Overall, higher immigration rates of small-bodied, winged species may result indirectly from their ability to fly.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, experimental data has revealed that M. soledadinus can survive flotation and exposures to saline conditions with half of the carabid beetles surviving flotation on seawater for ca. seven days (Renault, 2011;Hidalgo et al, 2013).…”
Section: the Start Of In-field Monitoring Of The Non-human Assimentioning
confidence: 99%
“…Several islands of the Golfe du Morbihan, rarely visited, may have been colonized by specimens of M. soledadinus by flotation on algae (Renault, 2011;Hidalgo et al, 2013) and even through ornithochory. Kerguelen shags Phalacrocorax verrucosus use seawrecks that they sometimes bring from one island to another to build their nests.…”
Section: Mid-1990s the Arrival Of M Soledadinus At The Scientific Rmentioning
confidence: 99%